2013
DOI: 10.1002/chem.201300358
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trisubstituted Ureas by a Multistep Sequence Utilizing Recyclable Magnetic Reagents and Scavengers

Abstract: Unprecedented magnetic borohydride exchange (mBER), magnetic Wang aldehyde (mWang) and magnetic amine resins were prepared from highly magnetic polymer-coated cobalt or iron nanoparticles. Microwave irradiation was used to obtain excellent degrees of functionalization (>95 %) and loadings (up to 3.0 mmol  g(-1)) in short reaction times of 15 min or less. A small library of ureas and thioureas was synthesized by the exclusive application of these magnetic resins. As a first step, a reductive amination of aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Improved extraction capacity (73%) was found for Co/C-PS-PAMAM G2 5, which can be ascribed to increased loadings of terminal amino groups made possible through the additional polystyrene layer on the surface of the NPs. 24,25,29,34,38 For both materials no signicant cobalt leaching was detected.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Improved extraction capacity (73%) was found for Co/C-PS-PAMAM G2 5, which can be ascribed to increased loadings of terminal amino groups made possible through the additional polystyrene layer on the surface of the NPs. 24,25,29,34,38 For both materials no signicant cobalt leaching was detected.…”
Section: Resultsmentioning
confidence: 94%
“…Carbon-coated nanobeads have proved their effectiveness in a variety of applications such as supports for scavengers, reagents or catalysts. [22][23][24][25][26][27][28] Relevant for this study, this type of nanoparticles was previously used for complexation/extraction of cadmium, copper, lead, 11 arsenic 29 ions as well as noble metal ions based on gold 19,30 and platinum. 30 However, no studies for the removal of mercury(II) from contaminated water were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Very interesting magnetic catalytic exchange resins were prepared by Reiser et al [ 69 ] using polymer coated cobalt and iron nanoparticles and microwave irradiation. The magnetic resins were employed to produce a library of ureas and thioureas using various reactions.…”
Section: Immobilisation Of Organic Catalysts Onto Magnetic Nanostrmentioning
confidence: 99%
“…Depending on the target of interest, different particle coating and functionalization strategies need to be developed to attach the target to the magnetic NP. 117,124 If we focus now on the use of magnetic NPs as magnetic separators in biological systems, the mechanism by which the separation agent works is the same as in wastewater applications; however, the target is different. 114,115 Water-stable magnetite/maghemite NP dispersions have been intensively researched for the treatment of wastewater based on their ability to act as magnetic separators.…”
Section: Magnetic Separationmentioning
confidence: 99%